2018
DOI: 10.5217/ir.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Development and diversity of lactic acid producing bacteria and bifidobacteria in healthy full term Indian infants from Himachal Pradesh

Abstract: Background/AimsThe initial microbial colonization is a crucial step for the healthy development of an infant. Previous studies from India reported the dominance of target microbial species among Indian infants without any analysis on the diversity of target groups. This is the first study from India with an objective to investigate the establishment and diversity of lactic acid producing bacteria (LAB) and bifidobacteria in vaginally delivered, full term, breastfed infants for the first 4 months after birth.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They found that among the lactic acid-producing bacteria, species of the genera Enterococcus, Streptococcus, and Lactobacillus were predominant, whereas among bifidobacteria, B. breve was the predominant species. The diversity of both lactic acid-producing bacteria and bifidobacteria increased with time over the 4 months of the study [69]. In a study performed in one of the leading hospitals of New Delhi, India, analysis of the fecal microflora of 29 full-term infants around 4 weeks of age revealed the presence of strictly aerobic, facultatively anaerobic, and anaerobic bacteria.…”
Section: Colonization Resistance and Pathogen Clearancementioning
confidence: 99%
“…They found that among the lactic acid-producing bacteria, species of the genera Enterococcus, Streptococcus, and Lactobacillus were predominant, whereas among bifidobacteria, B. breve was the predominant species. The diversity of both lactic acid-producing bacteria and bifidobacteria increased with time over the 4 months of the study [69]. In a study performed in one of the leading hospitals of New Delhi, India, analysis of the fecal microflora of 29 full-term infants around 4 weeks of age revealed the presence of strictly aerobic, facultatively anaerobic, and anaerobic bacteria.…”
Section: Colonization Resistance and Pathogen Clearancementioning
confidence: 99%
“…Bifidobacterium is commonly found in the vagina and the human digestive tract (Attri et al, 2018) as well as newborn digestive tracts (Penders et al, 2006). Bacterial colonization in the digestive tract begins during birth due to the infant contact to the vaginal tract and fecal microbiota (Palmer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…LAB and Bifidobacteria are acquired from the environment of which ingested food is presumably the main source. The group of bacteria that dominates the intestines in adult individuals is LAB, including Lactobacillus, Bifidobacterium, and Bacteroides (Attri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%